2011
DOI: 10.1002/cae.20359
|View full text |Cite
|
Sign up to set email alerts
|

Using learning style‐based diagnosis tool to enhance collaborative learning in an undergraduate engineering curriculum

Abstract: In this study, an intelligent learning style aware diagnosis agent for computer-supported cooperative learning is proposed. Learners are first assigned to heterogeneous groups based on their learning styles questionnaire given right before the beginning of learning activities on the e-learning platform. The proposed diagnosis agent then scrutinizes each learner's learning portfolio on e-learning platform and automatically issues feedback messages in case some learner's behavior that is unfitted to his/her lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Some team members might experience difficulties in communication, coordination, and interaction with other team members [12], mostly because of the lack of visual contact and body language. Therefore, one of the real strengths of computer supported collaborative learning is in the negotiation and interaction among peers through computer-supported social networks in which they seek to solve a problem together collaboratively [13], [14], [15]. A variety of studies in the field of mobile Computer Supported Collaborative Learning (mCSCL) have explored opportunities for designing learning applications through networked mobile technologies (e.g., [1], [6], [7], [8]).…”
Section: Enhancing Educational Practices Through Collaboration and Momentioning
confidence: 99%
“…Some team members might experience difficulties in communication, coordination, and interaction with other team members [12], mostly because of the lack of visual contact and body language. Therefore, one of the real strengths of computer supported collaborative learning is in the negotiation and interaction among peers through computer-supported social networks in which they seek to solve a problem together collaboratively [13], [14], [15]. A variety of studies in the field of mobile Computer Supported Collaborative Learning (mCSCL) have explored opportunities for designing learning applications through networked mobile technologies (e.g., [1], [6], [7], [8]).…”
Section: Enhancing Educational Practices Through Collaboration and Momentioning
confidence: 99%
“…Further, in an undergraduate engineering curriculum, [14] proposed an intelligent learning style aware diagnosis agent to analyze each student's learning portfolio and automatically issue feedback messages to enhance collaborative learning. Then, [23] promoted peer-learning to multi-layers in engineering courses and they found that peer tutors learned through reflecting on their own experience.…”
Section: Related Workmentioning
confidence: 99%
“…Huang et al [14] tried to develop an intelligent learning style aware diagnosis agent to dynamically analyze each learner's learning portfolio and then real-time issue feedback to notify his/her state of peer learning. However, regarding the analysis tools for peer learning, it is still under-researched.…”
Section: Analysis Toolmentioning
confidence: 99%
“…Among them, we can refer the proposal of learning sequenced by an application which bounds advance to new lessons until achieve some minimum marks in previous lessons [003]. Other works published on learning guided by computer application, are a system that generates messages to the students that not show progress on their work [002], and a system that helps to find the solution of guided exercises [007].…”
Section: Related Workmentioning
confidence: 99%